Direct investment in Asia by German small and medium-sized enterprises - Axel Borrmann (Intereconomics, 1996)
The tremendous importance of small and medium-sized enterprises within the German economy is repeatedly stressed in policy discussions. That makes the disproportionately low level of involvement by SMEs in the Asian growth region stand out all the more prominently. What are the factors inhibiting greater involvement? What form ought promotion programmes for SMEs to take?
Keywords: 330; Foreign Direct Investment